Transcriptional activity of ammonia oxidisers in response to soil temperature, moisture and nitrogen amendment - Chisholm, Chris; Di, Hong; Cameron, Keith; Podolyan, Andriy; Shen, Jupei; Zhang, Limei; Sirisena, Kosala; Che, Xueying (Frontiers in Microbiology, 2025)
The contrasting response of AOA, AOB, and comammox Nitrospira amoA transcript abundance to temperature, moisture, and nitrogen was investigated using soil microcosms. The moisture, temperature, and nitrogen treatments were selected to represent conditions typically found in a New Zealand (NZ) dairy farm. AOB dominated all synthetic urine treated soils. Peak AOB amoA transcript abundance was positively correlated with estimated soil ammonia availability. While AOB gDNA abundance and nitrification rate trends were similar. AOA were strongly influenced by soil temperature. At 20°C, AOA amoA peak transcript abundance averaged over 1 order of magnitude higher than at 8°C. Within the AOA community a member of the Nitrosocosmicus clade was positively correlated with ammonium and estimated ammonia concentrations. The presence and relative increase of an AOA community member in a high nitrogen environment poses an interesting contrast to current scientific opinion in NZ. Comammox Nitrospira abundance showed no correlation with soil moisture. This suggests that previously found associations are more complex than originally thought. Further research is required to determine the drivers of comammox Nitrospira abundance in a high moisture environment. Overall, these results indicate that AOB are the main drivers of nitrification in New Zealand dairy farm soils.